ANALISIS PERILAKU KONSUMEN TERHADAP PENGGUNAAN PLATFORM DIGITAL BANK (Studi Pada Generasi Z Kota Malang) - Calista Donabella, Belinda; Manzilati, Asfi (Contemporary Studies in Economic, Finance and Banking, 2022)
Technology and an increasingly developing economy that has an efficient impact on the use of cash. When using cash to transact with a large enough value it becomes inefficient. Crimes such as robbery, theft and counterfeiting cause people to have a fear of storing or carrying large amounts of cash. The purpose of this study was to determine how the influence of service quality, convenience, innovation, and trust on customer satisfaction in using the bank's digital platform. The research sample used was 200 people from Generation Z in Malang City. The research method used is a type of quantitative research with data analysis techniques using logistic regression. The results show that simultaneously service quality and convenience have an effect on customer satisfaction in using the bank's digital platform, while partially innovation and trust have no significant effect on customer satisfaction in using the bank's digital platform. banks need to increase innovation through digital banks they have and provide.